Human papillomavirus genotype distribution in low-grade squamous intraepithelial lesion cytology, and its immediate risk for high-grade cervical lesion or cancer: a single-center, cross-sectional study - Nida Jareemit; Navin Horthongkham; Suwanit Therasakvichya; Boonlert Viriyapak; Perapong Inthasorn; Mongkol Benjapibal; Vuthinun Achariyapota; Irene Ruengkhachorn (Obstetrics & Gynecology Science, 2022)
Objective To investigate the distribution of human papillomavirus (HPV) genotypes in low-grade squamous intraepithelial lesion (LSIL) cytology and the immediate risk of cervical intraepithelial neoplasia grade 2 or higher (CIN2+) lesions. Methods This prospective cross-sectional study enrolled women aged ≥21 years that were diagnosed with LSIL cytology at Siriraj Hospital (Bangkok, Thailand) during 2017–2019. Anyplex II HPV testing was performed to detect 14 high-risk HPV cases prior to colposcopy-directed biopsy. Results In total, 318 patients were included in the final analysis. Of those, 24 (7.5%), 241 (75.8%), 53 (16.7%) were aged 21–25 years, 25–50 years, and ≥50 years, respectively. Eighty-two patients (25.8%) had abnormal screening results within the previous 5 years. High-risk HPV infection was found in 188 patients (59.1%) with 127 (39.9%) having single and 61 (19.2%) having multiple infections. The five most common HPV genotypes were HPV 66 (18.6%), HPV51 (9.7%), HPV58 (9.4%), HPV16 (9.1%), and HPV56 (8.2%). The immediate risk of CIN2+ was 6% in LSIL, regardless of the HPV status, 8% in high-risk HPV-positive LSIL, and 3.1% in high-risk HPV-negative LSIL. When using 6% as the threshold risk for colposcopy, performing reflex HPV testing in LSIL cytology can decrease the number of colposcopies by 40.9%, with an area under the receiver operating characteristic curve of 0.6 (95% confidence interval, 0.5–0.7). Conclusion The study findings support the idea that geographic variations affect the HPV genotype. Reflex HPV testing may decrease the number of colposcopies in cytology-based screening regions with a high prevalence of low-carcinogenic HPV.